2007
DOI: 10.1080/14767050701437302
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal transport kinetics of carboplatin in the perfused human placental lobule:In vitrostudy

Abstract: We report for the first time that carboplatin transport from the maternal to the fetal circulation is relatively small in the human placenta at term. It is reasonable to assume that the risk for the neonate from carboplatin use in pregnancy is minimal when used in emergency clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Few investigators presented clinical data, which describe the evidence of transplacental tranfer of platinum derivates (19,21). The transport from the mother to the fetal circulation was limited, even in concentrations exceeding the therapeutic level (3,22). There are clinical data on 36 patients who received platinum-based chemotherapy during their pregnancy, among them seven patients who had cervical cancer (11).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Few investigators presented clinical data, which describe the evidence of transplacental tranfer of platinum derivates (19,21). The transport from the mother to the fetal circulation was limited, even in concentrations exceeding the therapeutic level (3,22). There are clinical data on 36 patients who received platinum-based chemotherapy during their pregnancy, among them seven patients who had cervical cancer (11).…”
Section: Discussionmentioning
confidence: 96%
“…Life-saving therapy for the mother poses life-threatening concerns for the fetus. Neoadjuvant chemotherapy followed by radical hysterectomy has been revealed to be an option for women with invasive cervical carcinoma during pregnancy; however, there is limited data wih regard to the potential toxicity and teratogenicity (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Experimental data suggest that platinum derivates have a mutagenic and teratogenic potential.…”
mentioning
confidence: 98%
“…To our knowledge, only three studies have reported placental transfer of platinum salt with the human placental perfusion model [ 75 , 78 , 79 ]. The only study on cisplatin placental transfer reported that cisplatin transport is negligible in the human placenta at term (13% of the value for antipyrine, the reference marker) [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The only study on cisplatin placental transfer reported that cisplatin transport is negligible in the human placenta at term (13% of the value for antipyrine, the reference marker) [ 75 ]. The same group used the human ex vivo model to assess placental transfer of carboplatin and found that the transport fraction also averaged 13% of the antipyrine transfer rate [ 78 ]. Thus, the authors suggested that there is minimal fetal risk when using cisplatin or carboplatin for pregnant patients.…”
Section: Resultsmentioning
confidence: 99%
“…55 Maternalfetal transport kinetics of carboplatin were studied ex vivo on perfused human placental lobules. 56 In that study, the transport of carboplatin from the maternal circulation to the fetal circulation was limited in the human placenta at term, even for concentrations of carboplatin exceeding twice the therapeutic concentrations. However, we discovered contradictory results in the current review: either detectable levels of cisplatin or platinum-DNA adducts were identified in 4 neonates who were exposed in utero to cisplatin and carboplatin, suggesting a late transplacental transfer of these drugs (Table 3).…”
Section: Transplacental Transfer Of Cisplatin and Carboplatinmentioning
confidence: 99%